Analisis Kualitas Larutan Mikroorganisme Lokal (MOL) Bonggol Pisang - NI KOMANG BUDIYANI; NI NENGAH SONIARI; NI WAYAN SRI SUTARI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
ABSTRACT Analysis of Local Mikroorganisme Solution Quality Based on Banana Weevil The experiment was conducted at the Soil Science and Environmental Laboratory, Faculty of Agriculture Udayana University in November 2014 until January 2015. The purpose of this research was to determine the effects of concentration and the length of banana weevil fermentation to the quality of local microorganism solution. The design of this research used a randomized group design with factorial pattern. The first factor was the banana weevil concentration which are consisted of of 3 levels such as 100 g, 200 g, and 300 g. The second factor was the length of fermentation, consisted of two, four and six weeks. Each treatment was repeated three times, so there were 27 trial in total. The observed parameters were : the nature of biological, physical and chemical solution of local microorganism. Physical characteristics including color and odor, biological properties by counting the total population of bacteria. Chemical properties including pH level, content of organic C, total-N, available-P and C/N ratio. The result of this research showed that the concentration amont and the length of fermentation had no significant effect on the total population of bacteria, pH, content of organic C, total-N, available-P and C/N ratio to the quality of local microorganisms solution. Keywords: Local Microorganisms , Banana Weevil, Concertation.